Epidemics and pandemics - Shoals, James; Kissock, Heather (Growth, development, and reproduction of the human body., 2021)
Explores the science behind epidemics and pandemics, and highlights well-known epidemic diseases such as Human Immunodeficiency Virus, Malaria, Polio, and Small Pox. Features information about the prevention of epidemic diseases and the World Health Organization. Includes color photographs, sidebars, an activity, a quiz, a glossary, and additional resources.